Thermo-catalytic decomposition of cotton seed press cake over nickel doped zeolite Y, hydrogen: enhanced yield of bio-oil with highly selective fuel-range hydrocarbons - Afraz, Marrij; Nisar, Jan; Shah, Afzal; Ali, Ghulam; Muhammad, Faisal; Anwar, Farooq; Wan Abdul Karim Ghani, Wan Azlina (Royal Society of Chemistry, 2024)
This research reports the yield of bio-oil from cotton seed press cake (CSPC) via an optimized thermo-catalytic pyrolysis using nickel impregnated zeolite Y, hydrogen catalyst. The catalyst, raw biomass and catalyst impregnated biomass were characterized using different analytical techniques. The ideal temperature, duration, and catalyst concentration for pyrolysis experiments were determined to be 300 °C, 20 minutes, and 5% of Ni-doped zeolite Y, hydrogen, respectively, in order to achieve the best bio-oil yield (35%). Gas chromatography-mass spectrometry (GC-MS) of pyrolytic bio-oil depicted the presence of C2-C26 hydrocarbons. The findings of this investigation showed that the synthesis of bio-oil with highly selective fuel-range hydrocarbons could be efficiently induced through the pyrolysis of CSPC biomass employing nickel impregnated zeolite Y, hydrogen catalyst. Moreover, thermogravimetric analysis (TGA) of cotton seed press cake with catalyst was carried out at various heating rates to find out the kinetic parameters. Employing Kissinger model, activation energy (Ea) and frequency factor (A) for various components of biomass i.e., hemicellulose, cellulose and lignin were calculated as 83.14 kJ mol−1, 99.76 kJ mol−1, 124.71 kJ mol−1 and 1.9 × 107 min−1, 1.0 × 108 min−1, 1.0 × 1010 min−1, respectively. It can be concluded from the results that cotton seed press cake waste has potential for use as a pyrolysis feedstock in large-scale bio-fuel production.